2020
DOI: 10.1158/1078-0432.ccr-19-3835
|View full text |Cite
|
Sign up to set email alerts
|

An FDA Review of Drug Development in Nonmetastatic Castration-resistant Prostate Cancer

Abstract: The US Food and Drug Administration (FDA) has approved three androgen receptor inhibitorsenzalutamide, apalutamide, and darolutamide-for the treatment of patients with nonmetastatic castration-resistant prostate cancer (nmCRPC). These approvals were all based on randomized, double blind, placebo-controlled trials demonstrating large improvements in metastasis-free survival (MFS) and internally consistent evidence of benefit seen across secondary endpoints. In this article, we summarize the FDA regulatory histo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 7 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…Since the CRPC growth depends on AR-signaling, targeting the AR is beneficial also in CRPC [ 25 ]. Important examples are the recently clinically approved AR antagonists Enzalutamide (Enz), Apalutamide (Apa) and Darolutamide that are used in therapy of mCRPC, mCSPC, and nmCRPC, respectively [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the CRPC growth depends on AR-signaling, targeting the AR is beneficial also in CRPC [ 25 ]. Important examples are the recently clinically approved AR antagonists Enzalutamide (Enz), Apalutamide (Apa) and Darolutamide that are used in therapy of mCRPC, mCSPC, and nmCRPC, respectively [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the Prostate Cancer Clinical Trials Working Group 3 defined nmCRPC as a progressively rising prostate-specific antigen (PSA) level, namely a 25% PSA increase from nadir (starting PSA ≥ 1.0 ng/mL), with a minimum increase of 2 ng/mL despite a tor-mediated transcription [15,16]. Between 2018 and 2019, the Food and Drug Administration (FDA) approved three second-generation ARi for nmCRPC [17]. These drugs are orally administered and their characteristics are summarized in Table 1.…”
Section: Definition Of Nmcrpcmentioning
confidence: 99%
“…In addition, the formers bind directly to the ligand-binding domain of the androgen receptor, inhibit its nuclear translocation, inhibit DNA binding, and impede androgen receptor-mediated transcription [15,16]. Between 2018 and 2019, the Food and Drug Administration (FDA) approved three second-generation ARi for nmCRPC [17]. These drugs are orally administered and their characteristics are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brave et al [21] showed similarities between these studies, such as phase III, doubleblind trials with 2:1 randomization of drug versus placebo; patients with PSADT ≤ 10 months (subgroup <6 months and ≥6 months); the allowed inclusion of pelvic adenopathies of up to 2 cm in the SPARTAN and ARAMIS studies; the authorized inclusion of patients who had or were receiving treatment with bone protective agents; conventional imaging techniques that were performed at baseline and every 16 weeks (thoraco-abdomino-pelvic CT or MRI and bone scintigraphy) to determine the absence of metastasis and disease progression, based on the response evaluation criteria in solid tumors (RECIST), version 1.1 [22]; and the main endpoints were MFS, overall survival (OS), and time to initiation of cytotoxic therapy.…”
Section: Pivotal Clinical Trialsmentioning
confidence: 99%